High Blood Ammonia Level Is a Predictor of Medium and Large Size Esophageal Varices In Cirrhotic Patients - Mia, Md Moshiur Rahman; Ullah, Parash; Rahut, Antora; Miah, Manjurul Haque; Rana, Mohammad Masud; Azam, Md Nur E; Mahmuduzzaman, Mohammad; Ghosh, Chanchal Kumar (Bangladesh Journal of Medicine, 2024)
Background: The development of esophageal varices (EV) and rupture of them are the most serious complications of portal hypertension. Upper gastrointestinal endoscopy is the gold standard for diagnosis of EV but it is a costly and troublesome invasive procedure. To find a non-invasive method for detection of size of EV and to predict the bleeding risk is appealing and would decrease the indications cost and discomfort of upper GI endoscopy. The aim of the study is to evaluate high blood ammonia level is a predictor of medium and large size of esophageal varices in Cirrhotic patients. Methods: This was an observational Cross-sectional study conducted on 40 cirrhotic patients in Department of Gastroenterology, BSMMU using a pre-designed data collection sheet. Information about clinical profile, laboratory parameters- blood ammonia, serum bilirubin, serum albumin, prothrombin time, and ultrasonography of abdomen, endoscopy upper GIT was collected and recorded. The collected data was analyzed by computer with the help of SPSS version 22. Statistical analysis was done by using appropriate statistical tool like Chi-square test, Student’s t- test. P value < 0.05 was considered as significant. Diagnostic efficacy of blood ammonia was calculated by using a value. Results: A total of 40 patients with cirrhosis. Mean age of cirrhotic patients were 47.47±12.98 years. Mean blood ammonia of small size EV of cirrhotic patients was 73.70±32.11 (μmol/L) and medium and large size EV was 118.3±38.37 (μmol/L) (P< .001). At the level of 78.5 (μmol/L), sensitivity and specificity of blood ammonia was 95% and 65% respectively in detection of size of EV. Conclusion: Blood ammonia estimation could be a good tool for identifying individuals with medium and large size esophageal who will need to undergo endoscopy more frequently. Bangladesh J Medicine 2024; 35: 167-172